Implementation Of The Kampung Family Planning Program In Percut Village, Percut Sei Tuan District, Deli Serdang - Desi Ariani (IHSA Institute, 2020)
The increasing population growth in Indonesia is a big problem facing the government. In addition, the weakening of the Family Planning program is not sufficiently capable in overcoming the problem of population growth in Indonesia so that efforts or innovations are needed to overcome these problems, so the Family Planning Village program was initiated which is one of the government's program innovations in strengthening the KKBPK program by narrowing the scope of targets, namely at the regional or village level. This research was conducted in Percut Village, Percut Sei Tuan sub-district, Deli district, Serdang North Sumatra. The method used in this research is descriptive research method with a qualitative approach. The key informants in this study were two people who were very familiar with the implementation of the Kampung KB program, namely the expert staff of the head of the North Sumatra BKKBN and the PLKB of Percut Village. The main informants consisted of two Percut villagers who felt the benefits of the KB Village program. An additional informant for this research is one community leader in Percut Village. Data collection techniques with literature study, in-depth interviews and observation. The data obtained in the field were then analyzed by researchers who explained qualitatively. Finally, conclusions can be drawn from the results of this study. The results of the study indicate that the implementation of the Kampung KB Program has not gone well, this can be seen from the implementation of this program which is no longer running and there are many shortcomings from various indicators including resources, inter-organizational relationships, and the disposition of the implementor. Suggestions in this study are the need to find a solution by implementing the Kampung KB program in re-activating the program and improving facilities, relationships between organizations and the disposition of the implementor to be better.